Market Behaviour, Arrivals, and Price Behaviour of Cumin in Mandor Market of Jodhpur District, Rajasthan - Verma, Vinod Kumar; Kumar, Pradeep; Kumawat, R. C. (Indian Journal of Marketing, 2014)
The present study was conducted in Jodhpur district of Rajasthan. Two tehsils, namely Looni and Falodi were selected on the basis of highest production and area. Six villages were selected randomly from the selected tehsils. The present study was carried out to ascertain the marketable surplus, sales pattern, market arrivals, and prices in the cultivation of cumin crop. Primary as well as secondary data were utilized in the study. The marketable and marketed surplus ranged between 95% to 97% on different sized farms. The sample farmers disposed of 85.74% surplus cumin seed in the Mandor regulated market, and only 14.26% of the surplus cumin seed was disposed in the villages to village traders. 53% was sold in the first quarter immediately after harvest (March to May), and the remaining 47% was marketed in the remaining three-quarters of the year (August to February). Small-size farmers disposed off their total surplus cumin seed in one lot as against the medium and large-size farmers, who disposed off their total surplus in two and more lots. It was noted that 63% of the cumin produce arrived in the first quarter (March-May) of the year. The arrivals were 17.93%, 8.54%, and 10.02% in the second, third, and fourth quarters. Farmers got 10.36% higher price by selling cumin in the second quarter over the post-harvest season (peak season or first quarter). Sale of cumin in the third and fourth quarters of the year was not found to be advantageous. The correlation coefficients between monthly wholesale prices and arrival of cumin in the corresponding months and in the subsequent months were -0.578 and -0.588, showing that there existed an inverse relationship between the two. The value of the correlation coefficients was estimated to be higher for the subsequent months than for the corresponding months. The value of the correlation coefficients between yearly arrivals and prices of cumin were negative in four years and was positive only in one year out of the five year study period.